Doobiedoo asks - Amago, Bambi Eloriaga; Amago, Roland (Makati City : Komiket, 2020)
Doobiedoo asks the funniest questions, but when he asks his parents "What's wrong with me?" $1 (Bit leads them to discover Doobie has autism. Parenting may be extra challenging, but it also leads to even greater rewards. "Doobiedoo Asks" is an Official Selection of the 1st Philippine International Comics Festival (PICOF2020), and winner of the 2022 National Children's Book Awards (Kids' Choice).s
Keywords: Autism spectrum disorders -- Comic books, strips, etc